Types of Dedolomitization - Ali, Khawaja Azam (Journal of Himalayan Earth Sciences, 1983)
Two types - centripetal and centrifugal dedolomitization is recognized. Petrographic evidence is provided to show that besides these two types, random formation of dedolomite also takes place.